Ecogeochemical characteristics of underground water of Ob-Tom Interfluve (Russia); SGEM. 15th International Multidisciplinary Scientific GeoConference; Bk. 1, Vol. 2 - Yankovich E. P. Elena Petrovna; Yankovich K. S. Kseniya Stanislavovna; Lgotin V. A.; Gulmina G. A. (Hydrogeology, Engineering Geology and Geotechnics, 2015)
Title screen